System Security Engineering and Feature‐based Product Line Engineering: A Productive Marriage. Issue 3 (8th October 2020) - Young, Bobbi; Darbin, Rowland; Clements, Paul
ABSTRACT: Product Line Engineering (PLE) is a systems engineering discipline to engineer a product portfolio using variation management techniques to take advantage of the products' similarities while managing their differences. It has well known cost, quality, and time to delivery improvements compared to single‐system development. Systems Security Engineering (SSE) is a discipline for engineering systems proactively and reactively mitigating vulnerabilities. Do these two engineering disciplines conflict with each other? Or are they compatible, even complementary? This article will discuss the relationship between PLE and SSE and how they work together. Specific topics include managing a product line factory of products in a secure way and implementing cyber resilient frameworks within a product line addressing cyber resiliency commonality and variability in product design, implementation, and migration over time.